Analisis Kualitas Tes dan Butir Soal UTS Pilihan Ganda Bahasa Arab Kelas III di SDIT Mutiara Global Kubang Raya Pekanbaru - Kiki Dewi Octaviani; Hikmah; Masrun (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2024)
The quality of the test greatly affects the accuracy of the test itself. Therefore, analysis of test quality is a step that must be taken to determine the degree of quality of a test, both the test as a whole and the items that are part of the test. In the assessment of learning outcomes, the test is expected to describe a sample of behavior and produce an objective and accurate value. The test used by the teacher must have good quality in terms of various aspects. Tests should be prepared in accordance with the principles and procedures for preparing tests, after use it is necessary to know whether the test is of good or poor quality. The type of this research is experimental research with a quantitative approach. To obtain data, of course, a tool or instrument is needed. The instrument used by researchers is a written test in the form of an objective test (multiple choice test) containing 10 questions in which there are questions to be answered by participants. The population in this study were all 3rd grade students of SDIT Mutiara Global Kubang Raya with a total of 52 people. From the results of the analysis using the ITEMAN (SPSS) Version 2.4 program, the items that were grouped well based on the level of difficulty were 2 items. From the results of the analysis using the SPSS version 2.4 program, the items categorized as very good in terms of differentiating power are 7 items, while those categorized as good enough do not need improvement are 2 items, those categorized as less good and need improvement are 0 items, and those categorized as bad are 0 items. Based on the results of the analysis using the ITEMAN program, there is one item that shows the ability of the test takers is low, namely in item 1. Based on the results of calculations using the help of the item output and Test Analysis program SPSS Version 2.4, the reliability test obtained a result of 0.950.